Batik Home Industry Wastewater Treatment Using UVC/Ozon Oxidation Method: Case Study in Cibelok Village, Pemalang, Indonesia. Issue 1 (March 2020) - Larasati, D A; Alkian, I; Arifan, F; Sari, S R
Abstract: Batik is one of Indonesia's cultural heritages that spread across various regions with their unique characteristics. One of the regions that have batik industries is Pemalang Regency. However, batik industries also contribute to liquid waste. Wastewater containing pollutants such as waxes, resins, dyes, and binders such as silicates produce high concentrations of Biochemical Oxygen Demand (BOD) and vibrant colors. There are still many batik enterprises that discard wastewater directly to the environment without being processed first. This study aims to degrade Remazol Black B and Biochemical Oxygen Demand (BOD) dyes in batik liquid waste to contact time variations 0, 15, 30, 45, 60 minutes with UVC-Ozone oxidation methods. The Ozone-UVC method is an alternative method for decolorization and degradation of BOD. The dye degradation test was carried out using Spectroquant UV/VIS Spectrophotometer, and the BOD degradation test was carried out using Dissolved Oxygen - DO Meter AZ-8403. The result shows that the BOD degradation at batik wastewater was from 190.17 – 96.83 mg/L. Visually, the increase in treatment time makes the sample look clearer (decolorization), evidenced by the sample image and decreased absorbance results.